Outbreak of mastitis in ewes caused by Streptococcus agalactiae - ZDRAGAS (Α. ΖΔΡΑΓΚΑΣ), A.; TSAKOS (Π. ΤΣΑΚΟΣ), P.; KOTZAMANIDIS (Χ. ΚΟΤΖΑΜΑΝΙΔΗΣ), C.; ANATOLIOTIS (Κ. ΑΝΑΤΟΛΙΩΤΗΣ), K.; TSAKNAKIS (Η. ΤΣΑΚΝΑΚΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Many cases of acute clinical mastitis, in seven neighboring sheep flocks of Larissa Prefecture, were investigated. The causative agent was identified by biochemical and serological tests as Streptococcus agalactiae. Further investigation of the isolates by pulsed-field gel electrophoresis (PFGE) revealed identical profiles. The results indicate that S. agalactiae should be considered as a significant pathogen that induces mastitis in ewes; the disease is characterized by high morbidity, easy transmission between ewes and rapid reduction in milk production. The antibiotic therapy proved to be ineffective, even though antibiotics administered after the sensitivity test, however, the administration of an autovaccine was promising.